1979
DOI: 10.3109/00365517909108863
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism in hypothermically perfused human kidney carcinoma: Incorporation rate of leucine into proteins

Abstract: Protein synthesis in tumour-involved human kidneys was studied before, during and after hypothermic perfusion. Before and after perfusion the incorporation rate of leucine into tumour and kidney cortex proteins was determined by incubation of tissue slices at 37 degrees C. During perfusion the incorporation of leucine from the perfusate into tumour and kidney cortex proteins was determined. Before hypothermic perfusion the incorporation rate of leucine into proteins at 37 degrees C was almost the same in kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…In five studies (5/30, 17%), the different groups did not have similar baseline characteristics or analyses were not adjusted for confounders 35,38,48,51,55 . Performance bias was rated as high in three studies, 31,34,40 low in one study, 42 and unclear in all others (26/30, 87%) 27–30,32,33,35–39,41,43–55 . Random housing of animals was not performed in two studies (2/30, 7%) 31,40 and was not reported in the remaining studies 27–30,32–39,41–56 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In five studies (5/30, 17%), the different groups did not have similar baseline characteristics or analyses were not adjusted for confounders 35,38,48,51,55 . Performance bias was rated as high in three studies, 31,34,40 low in one study, 42 and unclear in all others (26/30, 87%) 27–30,32,33,35–39,41,43–55 . Random housing of animals was not performed in two studies (2/30, 7%) 31,40 and was not reported in the remaining studies 27–30,32–39,41–56 .…”
Section: Resultsmentioning
confidence: 99%
“…Kidneys were retrieved from rats (21/30, 70%), rabbits (2/30, 7%), dogs (4/30, 13%), and more recently from pigs (3/30, 10%). A perfusion device, allowing ex situ kidney perfusion was used in all but four cases 27–51 . In the latter, the kidney was perfused in situ 52–54 or the perfusion method was unclear 55 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations